2017
DOI: 10.1209/0295-5075/117/20001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of amplitude chimeras in oscillator networks

Abstract: -We show that amplitude chimeras in ring networks of Stuart-Landau oscillators with symmetry-breaking nonlocal coupling represent saddle-states in the underlying phase space of the network. Chimera states are composed of coexisting spatial domains of coherent and of incoherent oscillations. We calculate the Floquet exponents and the corresponding eigenvectors in dependence upon the coupling strength and range, and discuss the implications for the phase space structure. The existence of at least one positive re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Throughout this paper we consider ω = 2 and use the following initial conditions [29]: x i = 1 and y i = −1 for 1 ≤ i ≤ N 2 and x i = −1 and y i = 1 for N 2 < i ≤ N. Figure 1A shows the phase diagram in the P − ε space: we can see that the amplitude chimera (AC) state is interspersed in between the completely synchronized oscillation zone (Sync) and the oscillation death (OD) zone. This is in accordance with the results of Zakharova et al [29], Schneider et al [52], Zakharova et al [53], and Tumash et al [54] where this system was studied in detail. Figures 1B-D illustrate the spatiotemporal evolution of the synchronized state (ε = 5), AC pattern (ε = 20) and multicluster OD state (ε = 30) at P = 10.…”
Section: Without Filteringsupporting
confidence: 92%
“…Throughout this paper we consider ω = 2 and use the following initial conditions [29]: x i = 1 and y i = −1 for 1 ≤ i ≤ N 2 and x i = −1 and y i = 1 for N 2 < i ≤ N. Figure 1A shows the phase diagram in the P − ε space: we can see that the amplitude chimera (AC) state is interspersed in between the completely synchronized oscillation zone (Sync) and the oscillation death (OD) zone. This is in accordance with the results of Zakharova et al [29], Schneider et al [52], Zakharova et al [53], and Tumash et al [54] where this system was studied in detail. Figures 1B-D illustrate the spatiotemporal evolution of the synchronized state (ε = 5), AC pattern (ε = 20) and multicluster OD state (ε = 30) at P = 10.…”
Section: Without Filteringsupporting
confidence: 92%
“…These authors have also found that for a random distribution without symmetries amplitude chimera states appear to be short transients towards in-phase synchronized region, while their lifetime may significantly increase for symmetric initial conditions. Further Tumash et al 35 have noted that the existence of at least one positive real part of the Floquet exponents indicates an unstable manifold in phase space, which explains the nature of these states as long-living transients. In the present study, we investigate the existence of transient amplitude chimera states and also analyze how such amplitude chimera states become stable with respect to an increase of nonisochronicity parameter.…”
Section: Study Of the Amplitude Chimera States And Imperfect Brementioning
confidence: 97%
“…The detailed study of the lifetime of AC states in Stuart-Landau oscillators is reported in Refs. 46 and 52. Note that in case of Stuart-Landau oscillators with symmetry-breaking nonlocal coupling large lifetimes can arise for certain values of the coupling range and strength due to the phase space structure, and they have been explained by a Floquet stability analysis 46 . In the present case, although the center of mass-shifted limit cycles are unstable, however, they are always trapped in between two symmetry-breaking bifurcation points PB1 and PB2.…”
Section: B Qualitative Explanation: Symmetry-breaking Bifurcationsmentioning
confidence: 99%
“…In amplitude-mediated phase chimeras (AMC) incoherent fluctuations occur in both the phase and the amplitude in the incoherent domain; also, in the incoherent domain the temporal evolution of the oscillators is chaotic. On the other hand, amplitude chimeras (AC) were discovered by Zakharova et al [44][45][46] where all the oscillators have the same phase velocity but they have uncorrelated amplitude fluctuations in the incoherent domain; Also, unlike AMC (or classical phase chimera), the dynamics of all the oscillators in the AC state is periodic.…”
Section: Introductionmentioning
confidence: 99%